The Rise of Agricultural Animal Welfare Standards as Understood Through a Neo-Institutional Lens - Ransom, Elizabeth (The International Journal of Sociology of Agriculture and Food, 2007)
In recent years agricultural animal welfare standards have increasingly been placed on the agenda of international, regional, and national governance bodies, as well as private agrifood organizations. Standards, long the domain of economists, are now recognized as one of the most significant emerging practices for governing food, and as such, a growing number of scholars have focused on the role that powerful actors have in setting standards and the distributional benefits of standards implementation. However, much of the existing literature relies on consumer-demand arguments for explaining the rise of animal welfare standards. This article uses sociological neo-institutionalism, specifically institutional isomorphism, to reveal that agrifood organizations are either forced by large food retailers, or by the demands of interacting with other complex organizations, to adopt animal welfare standards in an effort to maintain access to markets, political power and legitimacy. Further, due to the continuing uncertainty surrounding the definition of agricultural animal welfare and the standards and techniques used to ensure compliance, the evidence supports the theory that organizations will model themselves after similar organizations in their field that they perceive to be more legitimate or successful.